Study of factors predicting clinical outcomes of extracorporeal shock wave lithotripsy in Indian patients with upper urinary tract calculi - P. G., Panchal; Krishnaswamy, Mahesh; Dabhade, Dhammdeep C.; Swami, Onkar C. (International Surgery Journal, 2018)
Background: Extracorporeal shock wave lithotripsy (ESWL) is an effective non-invasive method for managing urinary tract calculi. Present study was undertaken to evaluate factors that may influence ESWL clinical outcomes in Indian patients with urinary tract calculi. Methods: This prospective study was conducted at Department of Urology, Medical Trust Hospital Cochin, India in the period from September 2006 to March 2009. Sixty patients with upper urinary tract lithiasis having stone size between 5 to 25 mm were included and patients with ˃2 calculi, distal ureteric obstruction (not relieved), renal anomalies were excluded. All patients were treated with DIREX medical system lithotripter. Clinical outcome of ESWL was assessed by factors like site, size, density and skin-to-stone distance. After statistical analysis, p-value ≤0.05 was taken as the level of significance. Results: The overall success of ESWL was 82%. The final success of ESWL for sites like ureter, pelvis, mid or upper and lower calyx were 94.1%, 84%, 85.7% and 58% respectively (p = 0.095). The rate of fragmentation of stone after one session of ESWL for stone size ≤10 mm, 11 mm - 20 mm and ≥21 mm was 76.5%, 68.4% and 16.7% respectively (p=0.009). For stone density 751-1000 HU, 22.2% patients required ≥2 sessions to achieve stone free status (p<0.0005). Around 15.6% patients in skin-to-stone distance (SSD) ≤10cm required ≥2 sessions to achieve stone free status (p = 0.27). Conclusions: ESWL should be considered a primary modality of treatment in patients with calculi size ≤20 mm, density ≤ 1000 HU, pelvic, ureteric and upper and/or middle calyceal calculi and for SSD ≤10 cm.